Neuroendocrine Tumors: A Focus on Liver Metastatic Lesions - LIMOURIS, GEORGIOS (Frontiers in Oncology, 2012)
Transhepatic radionuclide infusion (THRI) has been introduced as a new treatment approach for unresectable liver neuroendocrine metastatic lesions with the prerequisite of a positive In-111 Pentetreotide (Octreoscan). Patients with multiple liver neuroendocrine metastases can be locally treated after selective hepatic artery catheterization and infusion of radiolabelled somatostatin analogues, and in case of extra-hepatic secondary spread, after simple i.v. application. According to the world wide references, the average dose per session to each patient is 6.3±0.3 GBq (~ 160-180 mCi) of In-111-DTPA-Phe1- Pentetreotide, 10-12 fold in total, administered monthly or of 4.1± 0.2 GBq (~105-116 mCi) of Y-90 DOTA TOC, 3 fold in total or of 7.0 ± 0.4 GBq (~178-200 mCi) of Lu-177 DOTA TATE, 4-6 fold in total (the choice of which being based on the tumor size, assessed by CT or MRI) . Follow-up at monthly intervals has to be performed by means of ultrasonography (US). Treat- ment response has to be assessed according to the WHO criteria (RECIST or SWOG).